1996
DOI: 10.2307/2410668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intrinsic and Extrinsic Factors on Population Fragmentation in Three Species of North American Minnows (Teleostei: Cyprinidae)

Abstract: Geographic patterns of genetic variation (mitochondrial DNA [mtDNA] and allozymes) were used to examine effects of intrinsic characteristics (e.g., vagility, habitat specificity, and reproductive behaviors) and extrinsic factors (e.g., climatic and geological history) on population fragmentation. The three species of cyprinid fishes examined (Tiaroga cobitis, Meda fulgida, and Agosia chrysogaster) occupied similar historical ranges within the lower Colorado River drainage, but differ in intrinsic characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Samples from all locations were a subset of those analyzed in Dowling et al (1996a) with the exception of the Lake Mohave and upper Colorado River samples. The Lake Mohave sample was comprised of wild fish collected in 2000, and genomic DNA was extracted as described in Tibbets and Dowling (1996). Previous studies have identified hybridization with flannelmouth sucker (Catostomus latipinnis) in the off-channel bonds in the upper Colorado River.…”
Section: Samplingmentioning
confidence: 99%
“…Samples from all locations were a subset of those analyzed in Dowling et al (1996a) with the exception of the Lake Mohave and upper Colorado River samples. The Lake Mohave sample was comprised of wild fish collected in 2000, and genomic DNA was extracted as described in Tibbets and Dowling (1996). Previous studies have identified hybridization with flannelmouth sucker (Catostomus latipinnis) in the off-channel bonds in the upper Colorado River.…”
Section: Samplingmentioning
confidence: 99%
“…In particular, the presence (or absence) of an occurrence depends on the spatial scale of a record-a species may be absent from a specific reach but present in a river. In the arena of freshwater fish conservation, issues of scale are especially important because of the constrained connectivity in hierarchical river-creek networks (Dunham et al 1997) and because habitats suitable for particular fish species are often patchily distributed (Pringle et al 1988, Johnston 2000, resulting in substantial among-species variation in distributional fragmentation (Tibbets and Dowling 1996).…”
Section: Utilizing ''Scale-area'' Curves To Overcome Complications Ofmentioning
confidence: 99%
“…We used regional glaciation history and lineage history as a framework to evaluate associations between gene flow and life-history traits in darters. A number of studies have hypothesized that fecundity and dispersal related life-history characters influence migration and/or gene flow in fishes, and there is some empirical evidence supporting this relationship (Waples 1987;Doherty et al 1995;Tibbets and Dowling 1996). McAllister et al (1986) noted an association between body size and size of geographic range in North American freshwater fishes and suggested that body size positively influences dispersal capability and migration.…”
mentioning
confidence: 99%